Optimalisasi Strategi Numbered Head Together (NHT) dalam Meningkatkan Keterampilan Berbahasa Inggris Siswa SD N Cemagi - Juniartha, I Wayan; Sulatra, I Komang; Sari, Ni Putu Milla Supita; Ryasmi, Ketut Gita (Universitas Negeri Padang, 2025)
English is generally taught as a subject in schools with the aim of basic communication and honing the 4 language skills (listening, reading, writing, and speaking) in English with certain limitations. In improving students' ability to master English language skills, teachers can use strategies or methods in learning English. One of the methods used in English learning is NHT. This community service program aims at implementing the NHT strategy in improving the 4 language skills. The method carried out in this program is an implementation and training method conducted by some steps: observation, preparation, and practice. The result has shown that the program has been conducted successfully with the enthusiasm and participation of all students in completing all tasks in SD N 4 Cemagi. Besides that, the program has a heartwarming response from the teachers, parents, and Cemagi residences.